The Political-Religious Relations between the Kurds and the Ottoman Empire - Meirison Meirison (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
The Kurds are an ethnic group that has experienced significant friction with other countries, such as Persia, Arabia, the Mongols, and Turkey. However, the Kurds and the Ottoman Empire have established completely distinct relations, including the mutual attraction of the Islamic Faith, school of thought, and the problem of nationalism. Although Islam does not discern according to the ethnicity people belong to, it is a devotion that distinguishes their degree before God. Therefore, this article attempts to examine how the Kurds have been able to survive under the auspices of the Ottoman Empire, which was formerly considered as a substitute for the previous Islamic caliphate that ruled based on shari‘a. The study discovered that the political and legal transformation in the body of the Ottoman Empire made the Kurds extremely depressed and agitated. This brought about the rise of their nationalism and intention to establish an independent state. Unfortunately, it was difficult to realize since the region’s map is shaped by the winning countries of World War I, which did not recognize the so-called Kurdistan State. Also, the surrounding countries, such as Turkey, Iran, Syria, and Iraq, did not want to lose their territory.